Employee Retention Strategy Innovation Amidst Dynamic Challenges: A Literature Review - Hartadi, Agung; Wening, Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Employee retention is one of the major challenges faced by many business organizations today. Many industries face high demand for skilled workers, coupled with significant employee turnover rates. In the era of a knowledge-based society, human resources have become a major asset and competitive advantage for companies. High employee turnover rates negatively impact organizations, especially with the loss of talented talent, critical skills, and valuable institutional knowledge. In response to this challenge, companies are increasingly focusing on retaining high-performing employees rather than simply relying on costly replacement and retraining processes. Modern organizations recognize that one of the fundamental aspects of business management is the ability to motivate and retain employees, especially those who are able to survive changes such as organizational restructuring, downsizing, consolidation, reorganization, or reengineering initiatives. This study discusses human resource practices related to employee retention. This study uses a systematic literature type. The study aims to determine retention factors, challenges and strategies in employee retention. The results of this study are expected to be a basis for developing effective employee retention programs for various organizations. By implementing a comprehensive retention strategy supported by an adequate HCM program, companies can retain key employees who are the pillars of business success.